Land Value Determinants and Rental Values of Office Spaces in Ikeja, Nigeria - Olawande, Oni A.; Ayodele, Ajayi C. (Richtmann Publishing, 2011)
This study was carried out to examine the contributions of land value determinants to variability in rental values of offices inIkeja, Nigeria. In doing so, road network which has not received much consideration in studies on property value determinants, weredecomposed into its explanatory variables of quality, length, connectivity, and density, in addition to other variables like location, demand,accessibility, and supply of commercial properties in the study area. Multiple regression analysis of the data at 95% confidence levelshowed that accessibility (P-value=0.0045), demand (P-value=0.0022), supply (P-value=0.0115) ANOVA indicated 0.0423proving that road network have significant effect on rental value of office spaces in the study area. Similarly, step-wise regression analysisreturned four variables accessibility (0.0011), demand (0.0004), location (0.0413) and supply (0.0028) as the variables that actuallygreatly affect the rental values. The study has reinforced the importance of accessibility to development and investors wishing to embark onreal estate development should be conversant with the level of accessibility of the arterial roads along which such development will locate.Decision on the location of such development project should be based on a pragmatic approach such that selected locations would bring thehighest return that is adequate and sufficient to compensate investors.